16.14: Operational, ecological and economical assessment of steel railway bridges. (13th September 2017) - Zinke, Tim; Ummenhofer, Thomas; Lenz, Katrin; Schneider, Sarah; Beck, Tabea
ABSTRACT: Although for civil engineering structures commercial assessment approaches such as the British CEEQUAL [1] or the American Envision [2] can be found, no sustainability assessment system specialised in railway bridges exists. Here, system specific aspects like construction types, corrosion protection systems and construction processes must be considered. There is a lack of systematic research showing the advantages of prefabrication, and a small number of rehabilitation activities within the operation stage both leading to fewer obstructions of the railway network. Especially interdependencies of building activities and the operation of trains should be analysed and integrated into the assessment. The paper discusses the approaches and methods essential for a holistic assessment of railway bridges. The special boundary conditions of the rail traffic (compared to road traffic) will be presented. Based on this, economic and ecologic impacts throughout the entire life‐cycle are calculated and operation encumbrance costs caused by the interaction of construction sites and railway operation are shown. This is performed for three types of bridges: a thick plate through bridge, a composite bridge and a tied‐arch bridge.